Tetralogy of Fallot, Absent Vena Cava Superior, Persistent Left Vena Cava Superior, and Interrupted Vena Cava Inferior: A Case of Struggle in Open Heart Surgery - Hande İştar; Buğra Harmandar (Düzce Tıp Fakültesi Dergisi)
Interruption of vena cava inferior (VCI) is extremely rare, in occurrence in isolation or association with asplenia or polysplenia syndromes. In this abnormality, the infrahepatic segment of the VCI is absent, by representing the inadequacy of fusion of subcardinal embryological parts of the VCI. It is compensated by an azygos or hemiazygos vein that continues on the posterior wall of the thoracic cavity. In this case report, a case of incidentally diagnosed interrupted VCI in a patient diagnosed with tetralogy of Fallot (TOF), major aortopulmonary collateral artery (MAPCA), right arcus aorta, absence of right vena cava superior (VCS), and persistent left vena cava superior (PLVCS), and its successful surgical treatment was presented. If the hepatic vein confluence is of adequate size, the cannulation for cardiopulmonary bypass circuit through the hepatic vein confluence is safe in case of interrupted VCI.